Laparoscopy during the COVID-19 pandemic: Absence of evidence is not evidence of absence - Prabudh Goel; Ashoke K Basu (Wolters Kluwer Medknow Publications, 2020)
From a local outbreak to a global pandemic, the severe acute respiratory syndrome-coronavirus-2 infection has spread across 210 borders to infect 2.5 million humans. There is an organized disruption in the routine hospital functioning to divert the available resources for effective crisis management; most of the departments have been split to carve out a "COVID task force." The recommended indications for treatment of various medical conditions, medical procedures, and protocols have regressed on the evolutionary timeline. Newer recommendations are being released and updated regularly based on emerging evidence and experts' opinions. In view of exponential spread of the virus through routes already identified or those still elusive, the shedding of the virus during the incubation period, and lack of scientific evidence, the questions of "laparoscopy" or "no laparoscopy" assume importance. Herein, the evidence in literature pertaining to patient safety, efficient and effective utilization of hospital resources, and safety of health-care workers (HCWs) during the pandemic have been reviewed from the perspective of laparoscopy. The pathobiology of the virus including its survival properties and the different modes of transmission has been highlighted, and the relative risk to the HCWs between open and laparoscopic surgery dwelt upon. The recommendations from various international bodies have been discussed. Notwithstanding the absence of concrete evidence to exclude the possibility of bioaerosol-based transmission of the disease to the operating room staff, there is a multitude of other concerns which are addressed by avoiding the use of the laparoscope in the current scenario. Moreover, the absence of evidence is not evidence of absence; considering the high contagion and a long latent period associated with this virus, the onus is upon each individual surgeon to decide if one needs evidence of bioaerosol-based transmission or evidence in favor of safety before taking up 'laparoscopy' against 'open surgery'.